Urinary liver-type fatty acid-binding protein as a Marker for Early Diagnosis of Diabetic Nephropathy in Type 1 Diabetic Children. - M Abushady, Mones; A Fathy, Gihan; R El-alameey, Inas; Ma, Abbas; M Galal, Essam; A Nasr, Soha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: Renal failure and premature mortality are fatal prognosis of diabetic nephropathy. To improve patient outcome, early diagnosis of diabetic nephropathy is necessary. The study was designed to evaluate urinary liver-type fatty acid binding protein (L-FABP), as an early biomarker of tubulointerstitial injury, and its association with the clinical characteristics of type 1 diabetic children. Methods: Fifty randomly selected patients with type 1 diabetes mellitus (DM) attending the diabetes outpatient clinic of Ain Shams University Children's Hospital were included in the study. 50 age and sex-matched healthy subjects were enrolled as controls. Urinary L-FABP, 24 h urine albumin, hemoglobin A1c (HbA1c), serum creatinine, and lipid profile were measured. Results: Diabetic subjects had higher mean urinary L-FABP than controls (p<0.05). In microalbuminuric diabetic subjects, the mean urinary L-FABP was detected to be significantly higher than that in normoalbuminuric diabetic subjects, and significantly higher values of the mean urinary L-FABP were detected in the microalbuminuric and the normoalbuminuric subjects than the controls (p<0.05). Multiple linear regression analysis showed that duration of DM and HbA1c was the main predictors of urinary L-FABP in diabetic subjects. Conclusion: In patients with childhood-onset T1D, urinary L-FABP may be used as an indicator of renal injury in early stages of nephropathy, even in the normoalbuminuric state.